2008
DOI: 10.1007/s10661-007-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

Industrial effluent quality, pollution monitoring and environmental management

Abstract: Royal Commission Environmental Control Department (RC-ECD) at Yanbu industrial city in Kingdom of Saudi Arabia has established a well-defined monitoring program to control the pollution from industrial effluents. The quality of effluent from each facility is monitored round the clock. Different strategic measures have been taken by the RC-ECD to implement the zero discharge policy of RC. Industries are required to pre-treat the effluent to conform pretreatment standards before discharging to central biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…In Yanbu, several violations of industrial discharges have been reported (e.g. Paimpillil et al, 2002 andAhmad et al, 2008). Ahmad et al (2008) mentioned that many types of pollutants are discharged into coastal areas in excessive concentrations such as hydrocarbon compounds and thus present another form of pollution for Yanbu mangroves.…”
Section: Heavy Metal Accumulation In Red Sea Mangrove Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Yanbu, several violations of industrial discharges have been reported (e.g. Paimpillil et al, 2002 andAhmad et al, 2008). Ahmad et al (2008) mentioned that many types of pollutants are discharged into coastal areas in excessive concentrations such as hydrocarbon compounds and thus present another form of pollution for Yanbu mangroves.…”
Section: Heavy Metal Accumulation In Red Sea Mangrove Systemsmentioning
confidence: 99%
“…Paimpillil et al, 2002 andAhmad et al, 2008). Ahmad et al (2008) mentioned that many types of pollutants are discharged into coastal areas in excessive concentrations such as hydrocarbon compounds and thus present another form of pollution for Yanbu mangroves. In addition other organic and thermal pollutants were reported to significantly affect mangrove systems in other parts of the Red Sea coast (e.g.…”
Section: Heavy Metal Accumulation In Red Sea Mangrove Systemsmentioning
confidence: 99%
“…This forces the Saudi government to issue strict legislation concerning the quality of industrial wastewater effluents and the industries are not allowed to discharge any treated or untreated effluent in open channels and even after treatment, the reclaimed water must have to comply with direct discharge standards before discharge to the sea [2]. So the entire industrial sectors send their wastewater effluents to a local wastewater treatment plant to treat their waste effluents to an increasingly high standard.…”
Section: Introductionmentioning
confidence: 99%
“…Poor management of waste not only leads to declining environmental health conditions but contributes to disease outbreaks as well. Studies have indicated that solid waste management is a problem in many developing countries especially in high-density areas [1,2]. Effluent and other types of solid waste are dumped either in rivers or in drainages resulting into water and air pollu-…”
Section: Introductionmentioning
confidence: 99%